ANALISIS KEBUTUHAN MEDIA PADA MATA PELAJARAN PAI DI KELAS XI TKJ 1 SMK NEGERI 1 CEMAPAGA - Ramadhan, Ramadhan Wirayudha; Afrianto, Afrianto (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2023)
This article aims to explore the analysis of the need for instructional media in the subject of Islamic Education (PAI) in class XI of Computer Engineering and Networking (TKJ) 1 at State Vocational School 1 Cempaga. Amidst technological advancements and the era of education 4.0, it's crucial to understand how effective integration of instructional media can enhance students' interest and learning outcomes. In this context, the research adopts a qualitative descriptive method with a Research and Development (R&D) approach. Data were gathered through an online questionnaire distributed to eleventh-grade students, focusing on their preferences, understanding of PAI materials, and their needs for media in the learning process. The analysis results indicate that students require varied, engaging instructional media that incorporate images, videos, and simulations. From the analysis findings, the use of an E-Module is recommended as the optimal solution. An E-Module is an online learning module based on the internet, integrating various multimedia elements such as images, videos, and simulations. The implementation of this technology is expected to improve educational accessibility and enhance the effectiveness of the PAI learning process in class XI TKJ 1 at State Vocational School 1 Cempaga.